Procurement, Goods, Input Perancangan Sistem Infromasi Pengadaan Barang Berbasis Web Pada PT. Sintas Kurama Perdana Karawang - Rahmat Gunawan; Yahya Suherman; Nova Zakiatul Auliya (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
PT Sintas Kurama Perdana is the first formic acid producer in Southeast Asia. Inventory of finished goods is an important component in supporting the company's operational activities through sales activities. This research method uses qualitative methods by gathering various information and data needed to complete the inventory recording report. The procurement records inventory and invoices still using manual, which makes the process of releasing finished goods less effective. In this case so that the process of releasing goods can be done easily and quickly to avoid mistakes that occur in the process of recording and inputting, finished goods inventory using a web-based application.